Ischemic colitis: Who will survive? - Reißfelder, Christoph; Sweiti, Hussein; Antolovic, Dalibor; Rahbari, Nuh Nabi; Hofer, Stefan; Büchler, Markus W.; Weitz, Jürgen; Koch, Moritz (Surgery, 2011)
Background - Operative treatment for acute ischemic colitis is associated with a high morbidity and mortality. These patients often have a prolonged postoperative stay in the intensive care unit with an uncertain outcome. In this study, we aimed to develop a predictive risk score for perioperative mortality and to examine long-term follow-up of patients with acute ischemic colitis. - Methods - All patients (n = 177) undergoing surgical treatment for acute ischemic colitis in our institution from 2002 to 2008 were prospectively included in this study. Independent predictors of perioperative mortality and poor long-term survival were assessed by uni- and multivariate analysis. - Results - A risk score including various perioperative variables (nonocclusive ischemic colitis, acute renal failure, extent of bowel ischemia, serum lactate, and duration of catecholamine therapy) was defined being highly predictive for postoperative mortality of patients having undergone an operation for acute ischemic colitis. Mesenteric atherosclerosis in the surgical specimen is an independent prognostic factor for poor long-term survival (52 vs 40 months with mesenteric atherosclerosis; P = .027). - Conclusion - This study for the first time presents a risk score highly predictive of postoperative mortality of patients undergoing an operation for ischemic colitis. Our score may help to further select and modify therapeutic management in patients with acute ischemic colitis on the basis of validated data. Furthermore, we could demonstrate a significant influence of mesenteric atherosclerosis on long-term survival of patients with acute ischemic colitis.